PENGARUH EKTRAK KULIT MANGIS (Gracinia mangostan L.) TERHADAP JUMLAH RERATA SPERMATOSIT PRIMER TIKUS PUTIH JANTAN (Rattus Novergicus) Galur Spragua dawley YANG DIINDUKSI PLUMBUM ASETAT - I gede sugiana Karaeng; anggraini janar wulan; Hendri Busman (Medula, 2021)
The Pb metal content in motor vehicle exhaust gases can danger health and  damage the environment. Pb metal as a free radical can trigger oxidative stress. Oxidative stress causes an increase in reactive oxygen species (ROS) and damage to the spermatozoa membrane. Antioxidants are one of the compounds that can be used to overcome this problem, including the mangosteen peel extract which has a view of antioxidants as an antidote to free radicals. This experimental was conducted for 14 days. 25 male rats (Spragua dawley) were divided into 5 treatment groups: K + (without treatment), K-, P1, P2, P3 (exposed to plumbum acetate dose of 0.35gram / KgBB and given consecutively mangosteen peel extract at a dose of 0 , 50, 100, 200 mg / KgBB, mean primary sprematocytes were calculated using a microscope with 400x magnification. The results of the treatment analysis (P1, P2, and P3) showed that the mangosteen peel extract had not been able to increase mean primary spematocytes from male white rats, mean that of primary spermatocytes obtained was 133.2 ± 24 (K+), 71.85 ± 16.9 (K-), 72.0 ± 17.3 (P1), 29.2 ± 9.3 (P2), 43.3 ± 6.82 (P3)test post hoc LSD showed significant differences from each treatment group. The extract of the Mangosteen skin was not yet able to increase Average of primary spermatocytes of male white rats exposed to plumbum acetate.